Challenges in utilisation of small family norm - Pathak, Varuna; Chandra, Madhuri; Bisani, Veena Rathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: India is the most populous country in the world, sustaining 17.5% of the world’s population on 2.4% of the world’s surface area. Despite of India being the first country to formulate a National Family Planning Programme in 1952, the population of India continues to rise. Therefore a basic question arises, as to why do couple have a third child? For stabilization of population every couple must on an average have 2.2 children, but how far our family planning programmes having an impact on the beneficiaries, in terms of their ideologies and utilisation of the programme. To get answers to the above question the present study was undertaken with the following aims and objectives to determine the views about ideal family size and ideal spacing, to determine the degree of knowledge about various contraceptive methods, to know the family size amongst population not adopting small family norm and to know the reason for non-acceptance of family planning methods. Methods: This was a hospital based case control study. Cases were women with two live children and not practicing family planning. Controls included women who opted for family planning methods and adopted the two child norm. Both cases and controls were asked to fill up a questionnaire. Results: Most people practicing small family norm view ideal number of issues ≤ 2 i.e. 88% of males and 91% of females. 59.8% couples not practicing family planning, think ideal spacing ≤ 2 years. 100% controls had the concept of contraception. Conclusions: Desire for a male child in 30.6% cases is the most common reason for couples not following the 2 child norm.